PERANAN AUDIT INTERNAL TERHADAP PENGENDALIAN INTERN ATAS PERSEDIAAN BARANG DAGANG PADA PT. SUMBER MAKMUR ADIPRAYOGA BANDAR LAMPUNG - Yohannes Suharsana; Kristina Rianingsih (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2017)
The purpose of internal control can be achieved if the internal control elements are actuallyfulfilled and for such internal controls to run effectively and efficiently, a certain part that oversees andevaluates the internal control is required, that part is an internal audit.The purpose of in research is to know result and the big of role internal audit of internalcontrol over merchandise inventory.The type of research used in this study is descriptive research andcase study research, where the techniques used in collecting data is done through interviews,observation and filling questionnairesThe suggestion that can be given by the authors is internal audit must also perform an auditof the compliance of accounting principles so that companies are more guided by the applicableaccounting principles. Suggestions for internal control over merchandise inventory are companiesshould focus more on storing goods with company procedures.